2019
DOI: 10.1158/1055-9965.epi-18-0539
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Exposure among U.S. Adult Cigar Smokers: Population Assessment of Tobacco and Health (PATH) Study Wave 1 (2013–2014)

Abstract: Background: Given the diverse cigar market and limited data on biomarker patterns by cigar type, we compared biomarkers of nicotine and tobacco toxicants among cigar smokers and other groups.Methods: Using Wave 1 urinary biomarker data from 5,604 adults in the Population Assessment of Tobacco and Health (PATH) Study, we compared geometric mean concentrations among cigar-only smokers (all cigars and separately for traditional, cigarillo, and filtered cigars), cigarette-only smokers, dual cigar/cigarette smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…This cross-sectional study is a secondary analysis of existing data. Data came from wave 1 of the Population Assessment of Tobacco and Health (PATH) adult data [36][37][38]. Wave 1 of the PATH data used here were collected between 2013 and 2014.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional study is a secondary analysis of existing data. Data came from wave 1 of the Population Assessment of Tobacco and Health (PATH) adult data [36][37][38]. Wave 1 of the PATH data used here were collected between 2013 and 2014.…”
Section: Methodsmentioning
confidence: 99%
“…We also limited this sample to those who reported that they were pregnant at the time of the survey. The PATH study sample was drawn with a four-stage probability sampling design [36][37][38].…”
Section: Sample and Sampling Of The Path Studymentioning
confidence: 99%
“…This cross-sectional study borrowed data from the PATH-Wave 1 study (Chang et al, 2019;Hyland et al, 2017;Tourangeau, Yan, Sun, Hyland, & Stanton, 2018;Harlow, Stokes, & Brooks, 2018), a national survey of American adults sponsored by the U.S. Food and Drug Administration (FDA) and National…”
Section: Design and Settingmentioning
confidence: 99%
“…The PATH design, sampling, sample design, and measures are described elsewhere (Chang et al, 2019;Hyland et al, 2017;Tourangeau, Yan, Sun, Hyland, & Stanton, 2018;Harlow, Stokes, & Brooks, 2018).…”
Section: Design and Settingmentioning
confidence: 99%
“…The authors concluded that 2CYEMA is a reliable biomarker of tobacco smoke exposure, since the data indicated that 2CYEMA levels are consistent over time in cigarette smokers. In addition, data from the Population Assessment of Tobacco and Health (PATH) Study Wave 1 (2013–2014) showed that 2CYEMA levels in daily cigar-only smokers were comparable to those observed in daily cigarette-only smokers [ 15 ]. Another study examined the effect of concurrent use of combusted tobacco products and cannabis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%